Psychosocial factors as elements of influence in the decision to purchase insurance policies - Camejo Gotopo, César; Villalobos Colina, Daniel (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December)DO - 10.36779/mktdescubre/v#.#, 2019)
The purpose of the study is to analyze the psychosocial factors of influence in the purchase decision process of the users of car insurance policies, to answer the question, what are the psychosocial factors that influence the decision process for the purchase of insurance policies. car insurance? The question raised was addressed through the qualitative analysis of data stolen in the development of a focus group, in which the subjects constituted as reporting units, could freely express their perspective as buyer-users of different insurance companies located in the city of Maracaibo from Zulia state. Among the conclusions are that the users of car insurance policies generally make their purchase decision when they are previously stimulated by the recommendations of a credible or trusted person; they would even prefer to carry out a purchase or repurchase action without having a prior evaluation of the conditions and the added value in the services offered by the insurance company.